Błogosławieństwa w rycie hiszpańsko-mozarabskim i ich teologiczne znaczenie - Roszak, Piotr (Verbum Vitae, 2025)
The article examines the manner of celebration and the theological significance of blessings in the Spanish-Mozarabic rite, situating them within both historical and systematic contexts. It highlights the presence of numerous blessing rites in the Liber Ordinum, which articulate a request to subordinate human activities and situations to God’s power, invoking God’s blessing. Theologically, as articulated by Thomas Aquinas, this blessing represents a ‘multiplication’ of good in specific human situations. Additionally, the blessings contain elements of exorcism, which serve to liberate individuals from the influence of evil spirits. To elucidate the theological significance of these blessings, the article first analyzes the scope of blessings in the Liber Ordinum. It then explores the meaning of the blessing within the Mass, particularly the blessing given before the reception of Holy Communion and its connection to the sacrament. Finally, the article delineates the main theological ideas present in the prayers of the blessings in the Spanish rite.